2018
DOI: 10.1017/s0033291718002982
|View full text |Cite
|
Sign up to set email alerts
|

Joint factorial structure of psychopathology and personality

Abstract: BackgroundNormative and pathological personality traits have rarely been integrated into a joint large-scale structural analysis with psychiatric disorders, although a recent study suggested they entail a common individual differences continuum.MethodsWe explored the joint factor structure of 11 psychiatric disorders, five personality-disorder trait domains (DSM-5 Section III), and five normative personality trait domains (the ‘Big Five’) in a population-based sample of 2796 Norwegian twins, aged 19‒46.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
61
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 70 publications
11
61
2
Order By: Relevance
“…Future research might investigate the extent to which p extends to other behavioural domains. For example, suggestive evidence of links between p and personality has begun to emerge (Rosenström et al., ). In addition, instead of testing competing factor structures, we focused on the common pathway model, since the present study aimed to investigate the most parsimonious highest order part of the hierarchy that we call p. This is further justified by evidence for correlations and heterotypic sequential comorbidity across the internalising and externalising domains (Caspi & Moffitt, ).…”
Section: Discussionmentioning
confidence: 99%
“…Future research might investigate the extent to which p extends to other behavioural domains. For example, suggestive evidence of links between p and personality has begun to emerge (Rosenström et al., ). In addition, instead of testing competing factor structures, we focused on the common pathway model, since the present study aimed to investigate the most parsimonious highest order part of the hierarchy that we call p. This is further justified by evidence for correlations and heterotypic sequential comorbidity across the internalising and externalising domains (Caspi & Moffitt, ).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates were highest for measurements of the same trait at adjacent ages, around 0.50, and lowest between selfrated and maternally rated measures, around 0.20. The results of the univariate analyses in each cohort are displayed in eTables 10,11,12,13,14,15, and 16 in the Supplement.…”
Section: Cohort-specific Association Analysesmentioning
confidence: 99%
“…These include not only internalizing problems, such as depression and anxiety, 1,2 but also externalizing traits, such as attention-deficit/hyperactivity disorder (ADHD) and aggression. [3][4][5] Moreover, both in prospective and retrospective studies, behavioral and emotional problems during childhood and adolescence have been associated with other adult outcomes that are associated with adult mood disorders, including educational attainment (EA), [6][7][8][9] insomnia, 10,11 subjective well-being (SWB), 12 personality, [13][14][15][16] and body mass index (BMI; calculated as weight in kilograms divided by height in meters squared). [17][18][19] Both twin/family and molecular genetic studies have reported heritability [20][21][22] and stability [23][24][25] of psychopathology over time.…”
mentioning
confidence: 99%
“…Future research might investigate the extent to which p might extend to other behavioural domains. For example, suggestive evidence of links between p and personality have begun to emerge (Rosenström et al 2018).…”
Section: Discussionmentioning
confidence: 99%